Empirical Analysis of Subsidy Industrial Policy’s Effect on Export Innovation in the Chinese Manufacturing - Li, Bingqiang; Wang, Shan; Dong, Nannan; Li, Jinzhi; Li, Xi; Yu, He (SAGE open, 2023)
The relatively low export innovation capacity is not conductive to the steady transformation and upgrading of China’s manufacturing industry, and it is necessary to implement suitable policies to enhance export innovation capacity. This study empirically analyzes the data of 827,471 manufacturing enterprises from 2000 till 2013 to investigate the impact of subsidy policy on export innovation. The overall results show that China’s subsidy policy has a significant crowding-out effect on export innovation, and subsidy for relatively small enterprises is more conducive to promoting export innovation; however, enterprises’ independent investment does not own much impact on export innovation. The econometric results made from perspectives of the sub-region and the industry reveal that subsidy policy is not conducive to export innovation, independent investment is not beneficial to export innovation, and export innovation ability is positively correlated with enterprise scale, but the influence coefficient shows obvious differences.